The importance of bees for eggplant cultivations (Hymenoptera: Apidae, Andrenidae, Halictidae) - Patricio, Gleiciani Bürger [UNESP]; Grisolia, Bruno Barufatti [UNESP]; Desuoacute, Ivan Cesar [UNESP]; Montagnana, Paula Carolina [UNESP]; Brocanelli, Felipe Gonçalves [UNESP]; Gomig, Elizandra Goldoni [UNESP]; De Campos, Maria José Oliveira [UNESP] (My University, 2012)
The increasing demand for food and the Pollination crisis have emphasized the importance of better understanding the potential of different wild bee species for pollinating crops. The aim of this study was to investigate how dependent Solanum melongena L. is on bees for fruit production and if it is possible to observe any insufficiency of pollination in four (two organic and two conventional) eggplant cultivations. Bee samplings were performed during the eggplants peak flowering. Three pollination tests (Tl= without insect visitation; T2= free insect visitation; T3= Pollen complementation) were carried out in order to evaluate the importance of bees for fruit setting in S. melongena L. Most of the bee species collected on eggplant flowers were buzz-pollinators - Bombus, Xylocopa, Exomalopsis, Centris, Oxaea and many species of Halictidae, and can promote the eggplant pollination. Trigona sp. and Apis mellifera were also collected on flowers, but they can't vibrate their anthers, although Apis presented a flying adaptation while visiting the flowers and eventually can pollinate the flowers. Most of the unvisited flowers (Tl) failed to form fruits and when it happened, those ones were much lighter and smaller than those formed from flowers of T2 and T3; demonstrating the importance of bees for eggplant pollination. No statistical differences were found between the weight of eggplants in T2 vs. T3 within each area, however, the weight of fruits from T2 tests varied and differed significantly between the four studied areas. Our results indicated no pollen insufficiency in the studied areas, although the use of pesticides may disrupt crop-pollinator interactions, which may cause pollination insufficiency. Furthermore, land.